Cultivating Students' Entrepreneurial Readiness: A Systematic Study of the Role of Interest and Field Work Practice - Hilmi, Mohamad Alfin; Ekohariadi, Ekohariadi; Rijanto, Tri; Suhartini, Ratna (IKIP Widya Darma Surabaya, 2025)
Objective: The purpose of this study is to examine the relationship between entrepreneurial interest that arises in students and their readiness to become entrepreneurs through a systematic review of the literature. The analysis of the literature review aims to solve problems related to students' readiness to become entrepreneurs and their perceptions of student skills in productive subjects. Literature Study: A literature review analysis revealed the importance of entrepreneurial interest, independent learning, and productive skills as key factors in shaping vocational high school students' entrepreneurial readiness. These three factors support each other in developing students' abilities, motivation, and courage to start independent businesses. Findings: There is a relationship between fieldwork experience and entrepreneurial interests developed during school, leading to the creation of a generation of entrepreneurs. Students' readiness for entrepreneurship and their perceptions of productive skills are influenced by each individual's interest and independence in entrepreneurship. Novelty: Entrepreneurship is an alternative solution and effort to increase employment opportunities today. Readiness for entrepreneurship is influenced by entrepreneurial interest, personal independence, productive skills such as literacy, technical skills, interpersonal skills, and problem-solving, as well as the implementation of fieldwork practices in education. Fieldwork practices, an effective learning strategy, can encourage students to solve real-world challenges collaboratively, creatively, and responsibly.